The influence of trade union Disability Champions on employer disability policy and practice. (28th November 2014) - Bacon, Nick; Hoque, Kim
<x xml:space="preserve">Abstract</x> Disability Champions are a new type of lay workplace trade union activist, whose role is to encourage employers to audit and improve disability policies and offer independent advice and guidance on disability issues to employees. Drawing on a survey of the population of Disability Champions, this article assesses Disability Champion influence on employer disability policy and practice. While the majority of Disability Champions report having had a positive impact, they report greater influence on employer willingness to conduct disability audits and to amend and improve employer equal opportunities practices with regard to disability than employer willingness to make reasonable adjustments. The analysis also identifies several factors that are likely to be important in improving Disability Champion effectiveness. Overall, the results suggest Disability Champions have the potential to enhance the ability of unions to represent disabled people and help manage disability issues within the workplace. The article makes a theoretical contribution to Disability Champion roles by further developing the 'Activity‐Support‐Characteristic' framework for the antecedents of new union representatives' effectiveness.